PETANQUE SPORTS TRAINING AND SOCIALIZATION FOR PJOK TEACHERS IN MGMP SUKARAJA, KAB. SELUMA - Yarmani Yarmani; Defliyanto Defliyanto (DHARMA RAFLESIA, 2020)
This activity aims to introduce teachers and students to the latest sports games, namely Petanque sports. The activity is carried out during teacher and student learning hours. This activity is objectively or as-is with the subject of 25 Seluma MGMP teachers and 10 students. This activity lasted for 6 months, then held a closed seminar for 1 day. From the results of these activities show the great interest of teachers and students in recognizing petanque sports in schools seen from the questionnaire sheets generated by 18 points or presented at 90%, so that teachers and students are interested in developing and implementing these sports games so that in the future it can produce achievements that good.